THE MORAL PRINCIPLE OF PEACEKEEPING AND ITS PLACE IN UZBEKISTAN’S FOREIGN POLICY (TAMADDUN NURI JURNALI, 2025)
This article analyzes issues related to the impact of peacekeeping on the spiritual image of society and their role in ensuring the development and stability of society in the conditions of globalization, as well as the application of peacekeeping ideas in the development of a new society. Uzbekistan. Studying the causes and analyzing the consequences of threats aimed at disrupting the stability of regions and states, civil peace, and the well-being of society are noted as important factors of socio-spiritual development.